Investigation of the biochemical and apoptotic changes in breast cancer cells treated with leaf extract from tea (Camellia sinensis L.) grown with added boric acid - (:unkn) unknown (UNIV KARACHI, 2020)
Tea obtained from the leaves of Camellia sinensis L., a medicinal plant, is a widely popular beverage. Deficiency in boron, a micronutrient for C. sinensis, affects the growth as well as the quality of tea. The aim of this study was to explore whether boric acid at various concentrations added to soil improves the quality of C. sinensis and also whether it changes the apoptotic, anti-proliferative, and anti-oxidative effects of C. sinensis leaf extract on breast cancer (MCF-7) cells. C. sinensis was grown in Rize-Turkey. Boric acid at concentrations of 100 (group B), 300 (group C), and 500 (group D) mg/m(2) in sodium tetraborate buffer was administered as a single dose to the soil; group A (no boric acid) was the control. Boron, glutathione (GSH), malondialdehyde and protein carbonyl levels in the C. sinensis leaves were measured. C. sinensis leaf extracts at different concentrations was applied to MCF-7 cells for 24 and 48h Cytotoxicity, proliferation, and apoptosis were examined. The highest TUNEL+ cell percentage was in MCF-7 cells treated with D group leaf extract compared to the control group (p<0.001 at concentrations of 2.3, 2.6 and 3mg/mL). Moreover, the GSH level increased in the MCF-7 cells under the same conditions (p<0.001 for each concentration). Leaf extracts from C. sinensis grown in soil with boric acid have more anti-proliferative, apoptotic and anti-oxidative effects on the MCF 7 cells.
Keywords: Boric acid; Camellia sinensis; MCF-7; cell death; anti-oxidant; BORON; STRESS